Rural development in Stavropol Krai: Assessment based on statistics and local perception - Alexey N. Bobryshev; Andrey N. Baydakov; Olga S. Zvyagintseva; Sergey I. Lugovskoy (Russian Journal of Economics, 2023)
The article classifies rural territorial entities using the systems approach, which is based on identifying their key subsystems—natural, social, and economic. The study aims to develop and implement a procedure for creating a multi-aspect assessment range of rural development levels relying on the combined use of multivariate statistical analysis and the computational and expert comparison of objective and subjective structured information. The grouping of rural territorial entities carried out on this basis is intended to identify a pattern representing their targeted development, taking into account both the existing social and economic situation in the territory and its perception by the population. Methodological approaches to classify territorial rural units according to their level of rural development usually lack a systemic perspective and a subjective dimension to include the rural inhabitant perspectives. Using only expert opinions does not allow it to be reflected adequately enough. The comparison between the objective and subjective assessments of the natural, social, and economic conditions of rural territorial entities serves as the basis for identifying three groups of development patterns. Results were obtained through the combined application methods—cluster analysis and multidimensional scaling. The first one was used for an objective ranking of municipal districts in the region using official statistical data, while the second method was used for structuring the rural survey results. The main study result is the procedure for the multi-aspect grouping of rural areas, which enables the objective and subjective assessment of their key subsystems—economic, social, and natural—to be integrated into a single assessment tool. Its application helps establish a range of general patterns representing rural development. The study results can be used in the creation and updating of object- and subject-differentiated programs for the development of rural territorial entities.